2014
DOI: 10.5267/j.msl.2014.3.016
|View full text |Cite
|
Sign up to set email alerts
|

Building trust in e-banking and its effect on positive word-of-mouth advertising

Abstract: Nowadays, new technologies have changed the way of serving customers in many service organizations including banking industry. The importance of websites and their exclusive characteristics in presenting various kinds of services to the bank customers has increased. This paper presents a compound model to investigate the effect of traditional and online elements on customers' trust in electronic banking and word of mouth advertisement. For this purpose, a standard questionnaire based on Likert segmentation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…By building trust in eWOM advertising, companies give consumers the opportunity to believe in their information (Shaemi and Saneian, 2014). In Shaemi and Saneian’s study, it was shown that a consumer’s positive online experience encouraged positive WOM, which, in turn, increased trust in the company.…”
Section: Research Backgroundmentioning
confidence: 99%
“…By building trust in eWOM advertising, companies give consumers the opportunity to believe in their information (Shaemi and Saneian, 2014). In Shaemi and Saneian’s study, it was shown that a consumer’s positive online experience encouraged positive WOM, which, in turn, increased trust in the company.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The result provided evidence of the relationship that exists among the perceptions, the personal characteristics of the respondents and the organizational characteristics of their banks. Abadi and Nematizadeh (2012), Ahmadi and Afrouzi (2012), Azad, Abbaszadeh, Rikhtegar and Asgari (2013), Azad, Seyedaliakbar, Mousavirad and Mousavirad (2013), Esmaeili, Nazarpoori and Najafi (2013), Sanayei & Saneian (2013), Zadeh, Zangeneh and Azad (2014), Asgari, Ahmadi, Shamlou, Farokhi and Farzin (2014), Esmaeili and Horri (2014), Alikhani and Davarzani (2014), Shaemi and Saneian (2014), Yousefi and Nasiripour (2015), Arayesh (2015).…”
Section: Hussien and Abd El Aziz (2013) Egyptmentioning
confidence: 99%
“…Poon (2007) Characteristics Such as cost reduction, income increase and customer satisfaction which have motivated several organizations to benefit from competitive advantage resulting from electronic commerce. Shaemi and Saneian (2014) Reliability Refers to the extent to which a user believes that he or she can rely on the Ebanking service provided and feel satisfied with it. Lee & Lin (2005) Size…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation